Economically useful traits of heifers and cows of the Ukrainian black-and-white dairy breed of different origins and belonging to the genealogical formation - Voitenko, S.; Shaferivskyi, B.; Sydorenko, O.; Korobka, A. (Scientific Progress & Innovations, 2025)
The article investigated the growth characteristics of heifers of the Ukrainian black-and-white dairy breed of different origins by father, bull of the offspring, as well as by lineal affiliation to determine the individuals that grew most intensively and were able to engage in reproduction and milk production at an earlier age. A significant differentiation of the live weight of heifers during the growing process was established, which may be consistent with the heredity of the animals according to the Holstein breed, lineal affiliation and paternal origin. The best weight during breeding was characterized by the daughter descendants of the bulls of the Marshal 2290977 and Valiant 1650414.73 lines. In herds with traditional milk production technology, breeding of daughter descendants of the bulls of the Starbuck 352790.79 line is not desirable due to their slow growth and further exploitation in the process of milk production. To improve the intensity of weight growth of heifers of the studied lines, it is worth using animal selection taking into account the coefficient of variability of the trait, as well as the animals' belonging to the corresponding line, taking into account the coefficients of the influence of genealogical formation (26 % (P<0.001) on live weight and 23 % (P<0.001) on absolute and average daily gain. Heifers of different paternal origin were characterized by uneven growth during the growing period, but at the final stage, the highest live weight was achieved by the offspring of the bulls G. B. Halak Et 105889677, P. Kane Et 109010869, P. Manitoba Et 12529251, and S. O. Merlot Et 108013895. It has been proven that it is possible to predict the weight of heifers, daughters of the studied bulls, except for the daughters of bulls L. P. Kamik Et 105585416 and S. O. Merlot Et 108013895 at the age of 12 and 15 months, by their live weight at the age of 6 months, which reduces the signs of female selection. Daughters of all bulls, except Chapman Et 347903595, can be involved in reproduction at the age of 15 months or earlier, given their weight at this period. To form a highly productive herd and improve the breed, it is recommended to focus on such genetic factors as the line and bull, the father of the offspring, as well as to select animals using information about the variability of the trait, its connection with the desired productivity traits, taking into account the strength of the influence of the relevant genetic factors.